PERBANDINGAN KEBERHASILAN IMPLEMENTASI PROGRAM PAMSIMAS KAMPUNG PASAR PAGI DAN KAMPUNG TEGAL SARI DI NAGARI LUNANG SATU - Endah Kurnia; Lince Magriasti (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
The community-based drinking water and sanitation program (Pamsimas) is an innovation by the government in increasing public access to proper drinking water and sanitation with a community-based scheme for rural and peri-urban areas. Nagari Lunang Satu is one of the areas targeted by the Pamsimas III program. There was a difference in program success between Tegal Sari Village and Pasar Pagi during the implementation of the Pamsimas program in Nagari Lunang Satu. This research was conducted with the aim of knowing the differences in the successful implementation of the Pamsimas program in Pasar Pagi and Tegal Sari villages and to find out what factors caused the differences in the successful implementation of the Pamsimas program between Pasar Pagi and Tegal Sari villages. The research method used is quasi-qualitative research (quasi-qualitative). The results showed that the implementation of the Pamsimas program in Pasar Pagi Village was running optimally, while the implementation of the program in Tegal Sari Village was not running optimally. The factors causing the difference in the successful implementation of the Pamsimas program between Pasar Pagi and Tegal Sari villages are planning factors, community participation factors or attitudes, and coordination factors.